Review: Chemosensing of nutrients and non-nutrients in the human and porcine gastrointestinal tract. (7th August 2019) - Roura, E.; Depoortere, I.; Navarro, M.
Abstract : The gastrointestinal tract (GIT) is an interface between the external and internal milieus that requires continuous monitoring for nutrients or pathogens and toxic chemicals. The study of the physiological/molecular mechanisms, mediating the responses to the monitoring of the GIT contents, has been referred to as chemosensory science. While most of the progress in this area of research has been obtained in laboratory rodents and humans, significant steps forward have also been reported in pigs. The objective of this review was to update the current knowledge on nutrient chemosensing in pigs in light of recent advances in humans and laboratory rodents. A second objective relates to informing the existence of nutrient sensors with their functionality, particularly linked to the gut peptides relevant to the onset/offset of appetite. Several cell types of the intestinal epithelium such as Paneth, goblet, tuft and enteroendocrine cells (EECs) contain subsets of chemosensory receptors also found on the tongue as part of the taste system. In particular, EECs show specific co-expression patterns between nutrient sensors and/or transceptors (transport proteins with sensing functions) and anorexigenic hormones such as cholecystokinin (CCK), peptide tyrosine tyrosine (PYY) or glucagon-like peptide-1 (GLP-1), amongst others. In addition, the administration of bitter compounds has an inhibitory effect on GIT motility and on appetite through GLP-1-, CCK-, ghrelin- and PYY-labelled EECs in the human small intestine and colon. Furthermore, the mammalian chemosensory system is the target of some bacterial metabolites. Recent studies on the human microbiome have discovered that commensal bacteria have developed strategies to stimulate chemosensory receptors and trigger host cellular functions. Finally, the study of gene polymorphisms related to nutrient sensors explains differences in food choices, food intake and appetite between individuals.